(No^AROWANNYJ STRANNIK(B:s [(NpOWESTI I RASSKAZY(B] /s - (NlESKOW(B. (Nn(B.(Nas ((NmOSKWA(B:s (NhUDOVESTWENNAQ lITERATURA(B,s, 1981)
(Nw KNIGU WO[LI POWESTI I RASSKAZY RANNEGO PERIODA(B: "(NlEDI mAKBET mCENSKOGO UEZDA(B", "(NwOITELXNICA(B", "(NzAPE^ATLENNYJ ANGEL(B", "(No^AROWANNYJ STRANNIK(B" (NI (B"(NoDNODUM(B".s
rus
Keywords: (NpOWESTI I RASSKAZYs